2018
DOI: 10.1186/s13229-018-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances are associated with specific sensory sensitivities in children with autism

Abstract: BackgroundSensory abnormalities and sleep disturbances are highly prevalent in children with autism, but the potential relationship between these two domains has rarely been explored. Understanding such relationships is important for identifying children with autism who exhibit more homogeneous symptoms.MethodsHere, we examined this relationship using the Caregiver Sensory Profile and the Children’s Sleep Habits Questionnaire, which were completed by parents of 69 children with autism and 62 age-matched contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 55 publications
7
60
1
4
Order By: Relevance
“…The severity of these symptoms was predicted by the overall sensory responsivity as well as the social skills of participants. Specifically, higher sensory hyper-reactivity and lower social skills were associated with more severe insomnia, which is in close resemblance to findings in pediatric populations based on parent or caregiver reports (Liu et al 2006 ; Mazurek and Petroski 2015 ; Reynolds et al 2011 ; Tzischinsky et al 2018 ) and supports the notion that faulty entrainment of the circadian system associated with reduced sensory and social input could contribute to poor sleep in adults with ASD (Baker and Richdale 2017 ; Bourgeron 2007 ; Patzold et al 1998 ; Richdale and Schreck 2009 ). Interestingly, the effect of sensory reactivity seemed to be driven by the visual domain which was the only significant sensory predictor in a second analysis assessing the effect of the modalities smell, vision, hearing, touch, and taste.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The severity of these symptoms was predicted by the overall sensory responsivity as well as the social skills of participants. Specifically, higher sensory hyper-reactivity and lower social skills were associated with more severe insomnia, which is in close resemblance to findings in pediatric populations based on parent or caregiver reports (Liu et al 2006 ; Mazurek and Petroski 2015 ; Reynolds et al 2011 ; Tzischinsky et al 2018 ) and supports the notion that faulty entrainment of the circadian system associated with reduced sensory and social input could contribute to poor sleep in adults with ASD (Baker and Richdale 2017 ; Bourgeron 2007 ; Patzold et al 1998 ; Richdale and Schreck 2009 ). Interestingly, the effect of sensory reactivity seemed to be driven by the visual domain which was the only significant sensory predictor in a second analysis assessing the effect of the modalities smell, vision, hearing, touch, and taste.…”
Section: Discussionsupporting
confidence: 79%
“…Further, individual differences in light sensitivity have been shown to affect sleep in adolescents (Van der Meijden et al 2016 ). With respect to ASD, links between increased sensory responsiveness, decreased social skills and the presence of sleep problems have been reported previously in children and adolescents (Hollway et al 2013 ; Liu et al 2006 ; Mazurek and Petroski 2015 ; Reynolds et al 2011 ; Tzischinsky et al 2018 ). Interestingly, the effect of sensory responsiveness varied depending on the modality investigated with strongest associations in the tactile and auditory domain (Hollway et al 2013 ; Tzischinsky et al 2018 ) as well as the age group investigated with stronger effects for older children (Mazurek and Petroski 2015 ).…”
mentioning
confidence: 56%
“…Although not previously included in DSM‐IV, hyper‐ or hyporeactivity to sensory input are now part of the autistic symptomatology in DSM‐5 . Using a modality‐specific questionnaire for sensory sensitivity, Tzischinsky et al reported that sleep disturbances in children with ASD are associated with hypersensitivity and, to a lesser extent, hyposensitivity towards touch, which was not the case in the visual and auditory modalities. Interestingly, sensitivity to touch has been linked to altered GABA levels, which, as noted above, can explain difficulties in sleep initiation and maintenance in autism.…”
Section: Sleep Impact On Cognition and Sensory Processing: New Insighmentioning
confidence: 99%
“…While some have reported that sleep problems are more common in children with lower IQ 52 or higher autism severity 21,52 , others have not 16,20 . More consistent reports have shown that sleep problems are associated with increased selfinjury, anxiety, and aggression [18][19][20][21] as well as with sensory sensitivities [15][16][17][18] , thereby generating considerable challenges and difficulties for ASD children and their families 53 .…”
Section: Sleep Disturbances In Children With Asdmentioning
confidence: 99%
“…Symptoms include prolonged sleep latency, shorter sleep duration, and increased wake periods during the night, as reported by both subjective parental questionnaires and actigraphy measures [8][9][10][11][12][13][14] . Poor sleep in children with ASD is associated with increased sensory sensitivities [15][16][17][18] and increased aberrant behaviors [18][19][20][21] , which impair the quality of life of affected families 14 . PSG studies have corroborated the existence of sleep disturbances in children with ASD [22][23][24][25][26][27][28] , but have yielded mixed results regarding potential abnormalities in sleep architecture.…”
Section: Introductionmentioning
confidence: 99%